Towards Identifying Protective B-Cell Epitopes: The PspA Story - Khan, Naeem; Jan, Arif T. (Frontiers in Microbiology, 2017)
Pneumococcal Surface Protein A (PspA) is one of the most abundant surface molecules of Streptococcus pneumoniae (or pneumococcus). As an important structural and serological variable cell surface virulence factor, it evades complement-mediated phagocytosis of pneumococcus essential for its survival in the host. The cross-protection eliciting regions in the structure of PspA have been localized in the α-helical and proline rich regions of PspA. Recent data indicate significant variation in the ability of antibodies induced against different recombinant PspAs to recognize S. pneumoniae strains expressing distinct PspAs. Identification of topographical repertoire of B-cell epitopes that elicit a protective immune response seems essential in the engineering of a superior PspA based vaccine. Herein, we revisited the epitope identification in PspA and the advent of hybridoma technology in directing identification of protective epitopic regions of PspA, having potential to be exploited in the generation of potent vaccine.